Structural Features and Survey Results of the 18th-Century Illinska Church in Korop - Korzachenko, Mykola (Academic journal Industrial Machine Building Civil Engineering, 2025)
The article presents the results of a comprehensive study of the 18th-century Illinska Church located in the urban-type settlement of Korop, Chernihiv region, which is a valuable monument of Ukrainian Baroque architecture. The aim of the study was to identify the structural characteristics of the building and to determine the technical condition of its main elements. The research utilized archival materials that made it possible to reconstruct the history of construction and subsequent renovations, as well as data from on-site surveys conducted by the author during field expeditions.The main attention was focused on the analysis of the masonry walls, the wooden floor structure, and the metal tie rods that ensure the spatial rigidity of the building. It was established that the masonry consists of brick laid on a lime mortar and contains areas of material loss and wall cracking. The walls in the northern part of the church are 2 m thick, while those in the southern part are 1 m thick. The wooden structural elements of the floor are almost completely destroyed, with remaining fragments in an emergency condition. The metal tie rods embedded in the masonry are partly cut and are made of square steel bars with a cross-section of 4×4.5 cm, as well as steel strips measuring 7–8×1.0–1.5 cm. The study was carried out with the support of the Department of Urban Planning and Architecture of the Chernihiv Regional State Administration. The obtained results have practical significance for the further development of conservation and restoration guidelines for the church and are of scholarly interest in the context of studying traditional structural systems and their adaptation to modern operating conditions.